Appropriating Shakespeare contemporary critical quarrels - Vickers, Brian 1937- (Yale Univ. Press, 1993)
The last twenty years have seen an increasing fragmentation in Shakespeare studies, with the emergence of several critical schools, each with its own ideology, each convinced that all other approaches are deficient. In this important book, Brian Vickers argues that, in attempting to appropriate Shakespeare for their own purposes, each of these schools distorts the text by omission and misrepresentation. Two substantial opening chapters trace the derivation of current literary theory from the iconoclastic mood of l960s Paris. They show how an influential group of thinkers in the structuralist and post-structuralist tradition (Levi-Strauss, Barthes, Lacan, Althusser, Derrida, Foucault) promulgated a wholly negative concept of language, arguing that language cannot reliably represent reality; that literature cannot represent life; and that since no definitive reading is possible, all interpretation is misrepresentation. Vickers demonstrates that these attitudes have been decisively refuted, restates the central properties of language, and rehabilitates the notion of the author as creator of a literary work. At the core of the book he surveys the main conflicting schools in Shakespearian literary criticism - deconstructionism, feminism, new historicism, cultural materialism, and psychoanalytic, Marxist and Christian interpretations - describing the theoretical basis of each school, both in its own words and in those of its critics. Evaluating the resulting interpretations of Shakespeare, he shows that each is biased and fragmentary in its own way. Solidly researched, sharply argued and inevitably controversial, this book challenges many recent orthodoxies. As well as to theatre goers and readers of Shakespeare and Elizabethan drama, it will be of great interest to anyone concerned with modern literary theory.
Keywords: Shakespeare, William <1564-1616>; Shakespeare, William <1564-1616> -- Criticism and interpretation -- History -- 20th century; Shakespeare, William -- 1564-1616; Geschichte 1900-2000; Geschichte 1960-1990; Controversen; Engels; Interpretatie; Literatuurkritiek; Toneelstukken; Drama; Englisch; Geschichte; Literaturkritik; Criticism -- History -- 20th century; Literary quarrels -- History -- 20th century; Literature, Modern -- History and criticism -- Theory, etc; Literaturtheorie